ANALISIS PENGGUNAAN JARINGAN LAN PADA PT USDA SEROJA KOTA BATAM - Pastima Simanjuntak; Cecep Sugianto; Imam Asyarie (Universitas Putera Batam, 2018)
Usda Seroja Batam is one of the many companies that use computer network facilities. PT Usda Seroja Batam is in dire need of adequate network facilities to support two-way communication, namely employees with employees and employees with the company so as to create a good work environment to support all company activities. With the availability of a good computer network, data access speed is necessary. In accessing a data user or user wants fast access, but access speed is often constrained by the busy computer network used by all users or users in the company. The purpose of this research is to give perception how the use of LAN network at Usda Seroja Batam. The research method uses descriptive analysis that will obtain results from questionnaires that will be distributed to employees or network users in the company. From the results of descriptive analysis on the network, it will provide valuable information about the condition of a computer network